2015
DOI: 10.1038/jid.2015.130
|View full text |Cite
|
Sign up to set email alerts
|

Self-Antigen Presentation by Keratinocytes in the Inflamed Adult Skin Modulates T-Cell Auto-Reactivity

Abstract: Keratinocytes have a pivotal role in the regulation of immune responses, but the impact of antigen presentation by these cells is still poorly understood, particularly in a situation where the antigen will be presented only in adult life. Here, we generated a transgenic mouse model in which keratinocytes exclusively present a myelin basic protein (MBP) peptide covalently linked to the major histocompatibility complex class II β-chain, solely under inflammatory conditions. In these mice, inflammation caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
3
10
0
Order By: Relevance
“…We have recently demonstrated that DKK3 can act as a tissue-derived immune modulator that influences type and strength of local T cell responses in models of peripheral tolerance, transplantation, and autoimmune disease (27)(28)(29). We have found that DKK3 is expressed during kidney development, which occurs by a mesenchymal-epithelial transition.…”
Section: Introductionmentioning
confidence: 89%
“…We have recently demonstrated that DKK3 can act as a tissue-derived immune modulator that influences type and strength of local T cell responses in models of peripheral tolerance, transplantation, and autoimmune disease (27)(28)(29). We have found that DKK3 is expressed during kidney development, which occurs by a mesenchymal-epithelial transition.…”
Section: Introductionmentioning
confidence: 89%
“…However, MHC class II expression can also be induced on other cells, 96 including keratinocytes, by IFNγ 97‐99 . Keratinocytes expressing MHC class II can successfully present antigen epitopes to CD4 + T cells, 100,101 although it is unclear at what level of efficacy this actually occurs in human skin in vivo.…”
Section: Mechanisms Of Hf Ipmentioning
confidence: 99%
“…In addition, DKK3 expression was found in human MSCs ( 18 , 19 ). We recently identified DKK3 as a novel immune-mediator limiting CD8 + and CD4 + T cell-mediated responses ( 20 22 ). In a transgenic mouse model of peripheral T cell tolerance, we showed that CD8 + T cells, which were neonatally tolerized toward a self-antigen exclusively expressed on keratinocytes, expressed DKK3.…”
Section: Introductionmentioning
confidence: 99%